PROBLEMS OF TEACHING FOREIGN LANGUAGES AND EDUCATION QUALITY BASED ON ARTIFICIAL INTELLIGENCE IN THE MODERN EDUCATION SYSTEM. (Universal International Scientific Journal, 2026)
This article scientifically analyzes the issues of teaching foreign languages ​​based on artificial intelligence and the problems related to the quality of education in the process of introducing digital technologies into the modern education system. The study covers the integration of artificial intelligence technologies into the educational process, their didactic capabilities, and their role in increasing students' activity in the language learning process.
Keywords: artificial intelligence; digital education; foreign language teaching